The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0004-282x2007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Infecções em dispositivos neurológicos implantáveis em crianças e adolescentes

Abstract: RESUMO -Objetivo: Determinar a freqüência, as causas, o sítio específico e as manifestações clínicas e laboratoriais das infecções em crianças e adolescentes após a implantação de dispositivos neurológicos (DVP) no Hospital Governador João Alves Filho (Aracaju SE). Método: Estudo prospectivo, observacional, não controlado de 50 pacientes, submetidos a DVP (58 procedimentos), no período de janeiro de 2003 a outubro de 2004. Resultados: Observaram-se taxas de infecção por procedimento de 27,6%, taxas de infecção… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
5
0
4
Order By: Relevance
“…According to the literature, 70 to 80% of shunt infections occur within the first postoperative month and 15% occur from the first to the ninth postoperative month 4 . lima et al 4 reported a surgical infection rate of 27.6% (16/58) per surgical procedure and of 32% (16/50) per patient, with about 80% of cases being diagnosed within the first postoperative month. since the present patients were only studied for a short period of time, our infection rate is probably higher than reported in that study 3 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, 70 to 80% of shunt infections occur within the first postoperative month and 15% occur from the first to the ninth postoperative month 4 . lima et al 4 reported a surgical infection rate of 27.6% (16/58) per surgical procedure and of 32% (16/50) per patient, with about 80% of cases being diagnosed within the first postoperative month. since the present patients were only studied for a short period of time, our infection rate is probably higher than reported in that study 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Estudo prospectivo, observacional não controlado, realizado com 50 pacientes que foram submetidos à derivação ventricular peritoneal, determinou a frequência e as causas de infecção pós-implantação dos dispositivos. Destes foram destacados que a maior parte das infecções está relacionada à infecção do sítio cirúrgico, mostrando a necessidade de um olhar diferenciado aos profissionais que atuam diretamente nos cuidados do cateter, pois foi demonstrado pelo estudo que não houve alterações significativas quanto à idade, à etiologia da hidrocefalia, tipo de procedimento, tempo de internação pré-operatória, duração da cirurgia, antibiótico-profilaxia, cateter SNC prévio e índice de risco cirúrgico [17].…”
Section: Resultsunclassified
“…Even in the neonatal period shunting may be required. 14 Secondly according to the literature, VPS infections occur within the first 1-2 months after application of VPS 12,13 , so that, it is thought that this is the reason why shunt infections were observed more frequently in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…According to data reported from Turkey 1 , Portugal 14 and Korea 12 , shunt infection most commonly develops in the first 1-3 months after the shunt procedure. In our study; 70% of shunt infections developed within the first six months in accordance with the literature, but there was no statistically significant difference between early and late shunt infections except the patients' ages.…”
Section: Discussionmentioning
confidence: 99%